Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Adsorption of octadecyltrichlorosilane on Si(100)/SiO2 and SBA-15 - Mirji, S. A. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on Si(100)/SiO2 substrate and mesoporous SBA-15 has been studied by energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is used to study the adsorption kinetics of OTS on Si(100)/SiO2 and thermal stability of adsorbed OTS layer. Thermogravirnetric (TGA) technique is employed to understand the thermal behavior of OTS adlayer on SBA-15. Langmuir isotherms fit very well with OTS adsorption kinetics data on Si(100)/SiO2 and furnish adsorption rate constant, k(a) = 236 M-1 s(-1), desorption rateconstant, k(d) = 0.0082s(-1) and Gibbs free energy of adsorption, Delta G(ads) = -6.28 kcal mol(-1). EDAX and XPS results both show increased carbon content due to OTS adsorption and decreased oxygen and silicon content due to screening of these elements by OTS adlayer. FTIR data shows methylene (-CH2) and methyl (-CH3) stretching bands, in close agreement with reported data. The OTS layers are found to be thermally. stable up to a temperature of approximate to 260 degrees C on both Si(100)/SiO2 and SBA-15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Gibbs free energy; OTS; SBA-15; Self-assembly; Si(100)/SiO2; thermal stability